2018
DOI: 10.1029/2018gc007715
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Compaction Length on Radial Melt Segregation in Torsionally Deformed Partially Molten Rocks

Abstract: To investigate the influence of compaction length on radial melt segregation during torsional shear deformation of partially molten rocks, experiments were performed on samples composed of olivine plus ∼7 vol.% of either an albite, alkali basalt, or lithium silicate melt. These three melts cover a range of three orders of magnitude in viscosity, yielding samples that vary by approximately two orders of magnitude in compaction length. Samples were deformed in torsion at 1,473 K and 300 MPa in constant strain ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 43 publications
6
11
0
Order By: Relevance
“…Furthermore, analysis of rotary shear of a partially molten material yielded melt segregation at a broader, sample scale (Takei & Holtzman, 2009), consistent with results from experiments (Gourlay et al, 2007). This broader-scale segregation has recently been reported in torsion experiments on partially molten aggregates of olivine plus basalt (Qi et al, 2015;Qi & Kohlstedt, 2018;Kohlstedt et al, 2014). Further theoretical analysis of melt segregation in a number of different deformation geometries including simple shear flow, parallel-plate Poiseuille flow, torsional flow , and pipe Poiseuille flow (Allwright & Katz, 2014) demonstrated that, based on two-phase flow theory with viscous anisotropy, broad scale melt segregation is expected for the latter three deformation geometries.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, analysis of rotary shear of a partially molten material yielded melt segregation at a broader, sample scale (Takei & Holtzman, 2009), consistent with results from experiments (Gourlay et al, 2007). This broader-scale segregation has recently been reported in torsion experiments on partially molten aggregates of olivine plus basalt (Qi et al, 2015;Qi & Kohlstedt, 2018;Kohlstedt et al, 2014). Further theoretical analysis of melt segregation in a number of different deformation geometries including simple shear flow, parallel-plate Poiseuille flow, torsional flow , and pipe Poiseuille flow (Allwright & Katz, 2014) demonstrated that, based on two-phase flow theory with viscous anisotropy, broad scale melt segregation is expected for the latter three deformation geometries.…”
Section: Introductionsupporting
confidence: 85%
“…For compaction lengths smaller than the sample size, Allwright and Katz (2014) predicted that melt-rich sheets should extend inward from the channel wall inclined at a low angle and antithetic to the imposed flow direction, similar to those predicted and observed for general shear and torsional deformation geometries Holtzman et al, 2003;King et al, 2010;Kohlstedt et al, 2010;Qi et al, 2015;Qi & Kohlstedt, 2018). For compaction lengths smaller than the sample size, Allwright and Katz (2014) predicted that melt-rich sheets should extend inward from the channel wall inclined at a low angle and antithetic to the imposed flow direction, similar to those predicted and observed for general shear and torsional deformation geometries Holtzman et al, 2003;King et al, 2010;Kohlstedt et al, 2010;Qi et al, 2015;Qi & Kohlstedt, 2018).…”
Section: Melt Segregation In the Viscous Anisotropy Theorysupporting
confidence: 68%
See 1 more Smart Citation
“…Melt distribution also depends on the confining pressure; at high pressures (>1 GPa, >200 km depth in Io), it was shown that melt distribution corresponds to a disequilibrium phenomenon that can be caused by the non-hydrostatic state of stress or the induced strain (e.g., Bai et al, 1997;Jin et al, 1994). Recently, it was also demonstrated that compaction length has a strong influence on melt migration and extraction processes in a partially molten rock undergoing deformation (Qi and Kohlstedt, 2018). Understanding the rheological properties and dynamics of a melt-bearing mantle would strongly benefit from viscosity measurements under high pressure and temperature conditions (e.g., Liebske et al, 2005;Tinker et al, 2004) on molten analogues of Io's mantle.…”
Section: Experimental Work Needed: Dissipation In High Melt Fraction mentioning
confidence: 99%
“…Deformation and melt transport, including melt migration and segregation, are strongly coupled in partially molten rocks, as evidenced by field observations [1], laboratory experiments [2], and theoretical analyses [3]. Significantly, melt spontaneously localizes into melt-enriched bands oriented ∼20° to the shear plane, antithetic to the shear direction in partially molten rocks deformed in general and torsional shear [4][5][6][7]. The formation of melt-enriched bands is predicted and modeled by the two-phase flow theory with anisotropic viscosity [3,[8][9].…”
Section: Introductionmentioning
confidence: 97%